An Investigation into Provision for Students with Dyslexia in Primary School in England - Alsharif, Layla Mubarak (جامعة الإسكندرية - كلية رياض الأطفال, 2021)
This study investigates students with identified dyslexia/ specific literacy difficulties, the study depends on four main research questions revolve around the strengths and difficulties, of students with dyslexia/ specific literacy difficulties and how do these relate to their background factors, comparing between the progress and the level that the students have made over the last six months, students attitudes towards literacy classes and finally teaching methods and additional provision for students with dyslexi. Three students with dyslexia were selected, a classroom teacher, a special educational need coordinator and a teacher assistant. Data was collected through interview, observation and documents. The data from this study suggested that there were elements of good practice from which all on the school staff could learn, the data also suggested that support for literacy was observed in almost every classroom whether it was in the form of instructional templates to help students in their writing, word banks or the use or paired reading of passages in order to aid in comprehension. I would recommend that a programme of peer observation be undertaken to showcase best practice with regard to the teaching of literacy.
Keywords: عسر القراءة -- مهارات القراءة والكتابة -- مهارات الكتابة